2022
DOI: 10.21037/atm-22-1836
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of surgical and non-surgical treatments for traumatic optic neuropathy: a comparative study of 685 cases

Abstract: Background: The choice and efficacy of surgical or/and surgical treatments for traumatic optic neuropathy (TON) remained controversial by now. This study aims to present the outcomes of surgical and nonsurgical treatments for TON in our center.Methods: A total of 685 consecutive patients were retrospectively included in the study. And divided into surgical and non-surgical groups. All cases were treated with corticosteroids for 3 days after admission.Endoscopic optic decompression was applied to 479 patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Different researchers published their surgical techniques to treat TON [ 86 – 88 ]. Wang Wei et al found that endoscopic optic nerve decompression combined with corticosteroids achieved better visual outcomes in patients with no light perception [ 89 ]. In a study by Li et al, 71% of patients treated within a week of injury showed improved vision after extracranial optic nerve decompression [ 90 ].…”
Section: Surgical Managementmentioning
confidence: 99%
“…Different researchers published their surgical techniques to treat TON [ 86 – 88 ]. Wang Wei et al found that endoscopic optic nerve decompression combined with corticosteroids achieved better visual outcomes in patients with no light perception [ 89 ]. In a study by Li et al, 71% of patients treated within a week of injury showed improved vision after extracranial optic nerve decompression [ 90 ].…”
Section: Surgical Managementmentioning
confidence: 99%
“…In some studies, it is observed that, based on the assumption, some patients may have spontaneous vision recovery due to natural healing processes or collateral circulation. Mild visual loss in patients may need treatment in cases of presentation contraindications to corticosteroids or surgery or a preference for noninvasive management (20). We need to keep in mind that it is advised to have Observation towards patients may also be indicated for patients with direct (TON) from penetrating injury or complete transection of the optic nerve, as these cases have poor prognoses regardless of treatment.…”
Section: Managementmentioning
confidence: 99%
“…[9] However, some studies have reported that surgical decompression is more effective than steroid therapy alone because it relieves the constriction of the optic nerve in the osseous structure, especially in cases of optic canal swelling due to edema, hematoma, or nerve swelling. [3,14] However, surgical results vary because there are no reliable criteria for surgical indication. [15] We report a unilateral TON case complaining of blindness showing approximately 50% visual-evoked potential (VEP) activity, where VEP had begun to recover immediately after decompression during OCD operation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] However, some studies have reported that surgical decompression is more effective than steroid therapy alone because it relieves the constriction of the optic nerve in the osseous structure, especially in cases of optic canal swelling due to edema, hematoma, or nerve swelling. [ 3 , 14 ] However, surgical results vary because there are no reliable criteria for surgical indication. [ 15 ]…”
Section: Introductionmentioning
confidence: 99%